HOW BEHAVIORAL ECONOMICS INFLUENCES FINANCIAL EDUCATION - Alin ISTOCESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
Financial education tied with behavioral economics can result in a new way of looking at how to improve the skills and attitudes of people, whether when budgeting, saving, or investing. It provides a new perspective on why it it necessary to study view the way people act when spending. Even though each person is unique, the behavioristic patterns are not so unique. Some people tend to spend chaotically or on impulse, while others tend to be generally very organized when it comes to money. This paper shows a set of findings done in these two fields.